Male Leadership (Husband) in the Household in Surah An-Nisa, Verse 34 (Comparative Study of Tafsir Mafatih Al-Ghayb by Fakhr Al-Din Al-Razi and Tafs?r Al-Man?r by Muhammad Abduh) - Islamiyah, Islamiyah; Lutfianto, M.; Bevoor, Bevoor; Yingxiang, Schunk (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2021)
The understanding of male leadership (husband) in the household according to the Qur'an in Surah an-Nis?' verse 34 both classical and contemporary mufassirs have different opinions. The existence of a long time span from the time of the Prophet Muhammad as the initial mubayyin of the Qur'an to the present must have changed. Because it has implications for changes in socio-cultural conditions. This research is a descriptive-analytical-comparative qualitative research. Library Research is a research study in which the materials or data used come from the library in the form of books, encyclopedias, journals, documents, magazines and so on. From the analysis of the data collected through the methods used, this study answers that leadership in al-Qur'an letter al-Nis?' verse 34, al-R?z? interprets it with power, while according to Muhammad Abduh the leadership is interpreted in responsibility. In the sense that if a man is able to be responsible in fulfilling the rights of a wife then it is appropriate that the leadership is in his hands